Boundary handling and porous flow for fluid–hair interactions. (November 2015) - Lin, Wei-Chin
Abstract: We present a two-way coupling technique for simulating the complex interaction between hair and fluids. In our approach, the motion of hair and fluids is simulated by evaluating the hydrodynamic forces based on boundary handling techniques used in SPH (Smoothed Particle Hydrodynamics) fluids. Water absorption inside the hair volume is simulated with a diffusion process by treating the hair volume as porous media with anisotropic permeability. The saturation of each hair strand is then used in boundary density estimation as well as fluid–boundary force computation to greatly stabilize the simulation. We also utilize the saturation of hair to derive the adhesive force between wet hair strands. This enables us to simulate the formation of hair clumps dynamically without the need to employ post clumping processes. As a result, the proposed method realistically reproduces subtle fluid–hair interactions and can be easily applied to any SPH fluid as well as hair solvers. Abstract : Graphical abstract: Abstract : Highlights: A generic two-way coupling technique for simulating hair-fluid interactions is proposed. Water absorption inside hair volume is considered to evaluate the hydrodynamic forces. Hair clump formation is achieved by a self-adhesive force between wet hair strands. The proposed technique has been validated on different fluid solvers.